Characterization of peptide O⋯HN hydrogen bonds via1H-detected 15N/17O solid-state NMR spectroscopy. Issue 21 (21st February 2023) - Hung, Ivan; Mao, Wenping; Keeler, Eric G.; Griffin, Robert G.; Gor'kov, Peter L.; Gan, Zhehong
Abstract : Sensitive high-resolution multidimensional solid-state NMR method is reported for facile identification of hydrogen-bonded 15 N– 17 O pairs in peptides. Abstract : High sensitivity and resolution solid-state NMR methods are reported, that straightforwardly select hydrogen-bonded 15 N– 17 O pairs from amongst all other nitrogen and oxygen sites in peptides, to aid protein secondary and tertiary structure determination. Significantly improved sensitivity is obtained with indirect 1 H detection under fast MAS and stronger relayed dipole couplings.